2014
DOI: 10.1016/j.carbpol.2013.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Application of different feeding strategies in fed batch culture for pullulanase production using sago starch

Abstract: The production of pullulanase by Bacillus flavothermus KWF-1 in batch and fed batch culture were compared using 2L bioreactor. In batch culture, 0.0803 U/mL of pullulanase activity with specific activity of 0.0213 U/mg was produced by controlling the agitation speed and temperature at 200 rpm and 50 °C, respectively. Fed batch production was studied by feeding the culture with different sago starch concentrations in various feeding modes for enhanced pullulanase production. Exponential feeding mode at dilution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Pullulanase production has been well-studied in recent years because of its extensive application in the food and chemical fuel industries [ 24 ]. Pullulanase has been expressed in E. coli [ 23 ], B. subtilis [ 25 ], B. flavothermus [ 26 ], B. licheniformis [ 27 ], Brevibacillus choshinensis [ 24 ], Pichia pastoris [ 28 ] and Saccharomyces cerevisiae [ 29 ]. Expression levels are high in E. coli, but the use of E. coli is restricted in industrial food applications because of its potential pathogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…Pullulanase production has been well-studied in recent years because of its extensive application in the food and chemical fuel industries [ 24 ]. Pullulanase has been expressed in E. coli [ 23 ], B. subtilis [ 25 ], B. flavothermus [ 26 ], B. licheniformis [ 27 ], Brevibacillus choshinensis [ 24 ], Pichia pastoris [ 28 ] and Saccharomyces cerevisiae [ 29 ]. Expression levels are high in E. coli, but the use of E. coli is restricted in industrial food applications because of its potential pathogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…P ullulanase (EC 3.2.1.41), which catalyzes the hydrolysis of ␣-1,6-glucosidic linkages in pullulan, amylopectin, and the dextrins of amylopectin, is a well-known starch-debranching enzyme (1). It belongs to the ␣-amylase family, which is identified as glycoside hydrolase family 13 in the CAZy database.…”
mentioning
confidence: 99%
“…Bence (2011) with comparison of two CFRs of 0.125 and 0.40 l/h showed that increase of dilution rate by the adding fed-batch bioreactor volume at a higher CFR (0.40 l/h) led to a significant improvement in glucose consumption and biosurfactant production by Bacillus subtilis. Shankar et al (2014) also found that the use of an ideal dilution rate can significantly supply high amounts of biomass and pullulanase synthesis by Bacillus flavothermus KWF-1 under constant feed rate mode.…”
Section: Analysis Of Influence Of Variables On the Cell Mass And Pigm...mentioning
confidence: 90%